1994
DOI: 10.1051/jp4:19945134
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation du timbre des sons complexes.II. Analyses acoustiques et quantification psychophysique

Abstract: A timbre space represents the mental organization of sound events at equal pitch, loudness, and duration. The geometric distance between two timbres corresponds to their degree of perceived dissimilarity. The dimensions of such a three-dimensional space, established by Krumhansl [l] for a set of 21 synthesized sounds, were investigated with respect to their acoustic characteristics. Several acoustical parameters based on the temporal and frequency properties of the sounds were calculated. The high degree of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 5 publications
2
60
0
6
Order By: Relevance
“…Attack time separates impulsive from sustained instruments, and spectral centroid reflects the global spectral distribution. Other parameters have been less systematically reported: spectrum fine structure (Krimphoff, McAdams, & Winsberg, 1994), spectral spread (Marozeau et al, 2003), or spectral flux (McAdams et al, 1995), the latter being a measure of the variation of the spectrum over time. Altogether, these studies confirm that timbre indeed comprises several perceptual dimensions, with each of these dimensions corresponding to a single acoustic parameter.…”
Section: Behavioral Studies Of Timbre Perceptionmentioning
confidence: 99%
“…Attack time separates impulsive from sustained instruments, and spectral centroid reflects the global spectral distribution. Other parameters have been less systematically reported: spectrum fine structure (Krimphoff, McAdams, & Winsberg, 1994), spectral spread (Marozeau et al, 2003), or spectral flux (McAdams et al, 1995), the latter being a measure of the variation of the spectrum over time. Altogether, these studies confirm that timbre indeed comprises several perceptual dimensions, with each of these dimensions corresponding to a single acoustic parameter.…”
Section: Behavioral Studies Of Timbre Perceptionmentioning
confidence: 99%
“…Grey (1977;Grey & Gordon, 1978) used MDS techniques to derive a three-dimensional perceptual model of timbre, with the first dimension related to the spectral energy distribution of the sounds and with the remaining two axes corresponding to the degree of temporal synchronicity in the rise and decay of the upper harmonics and to the degree of spectral fluctuation in the signal envelope. Krimphoff, McAdams, and Winsberg (1994) reanalyzed a three-dimensional space obtained with synthetic sounds by Krumhansl (1989), and they found the following acoustic correlates for the dimensions: (I) the centroid of the sound spectrum, (2) the logarithm of the rise time, and (3) the "spectral flux" corresponding to the standard deviation of the time-averaged harmonic amplitudes from the sound's spectral envelope. Critical dynamic cues need not be present only in the rise portion of a tone but can occur throughout its duration (Iverson & Krumhansl, 1993;Wedin & Goude, 1972).…”
mentioning
confidence: 99%
“…In addition to the W/H ratio, we found that the subjects also discriminated the bars on the basis of their spectral centroids (i.e., the center of gravity of the sound spectrum, expressed as amplitude-weighted mean frequency). The spectral centroid (SC) for the attack portion of each sound was computed using the following formula (after Krimphoff, McAdams, & Winsberg, 1994): Values for An were calculated using two different types of spectral information: (1) all spectral components within 50 dB of the maximum signal amplitude, averaged separately for four time periods, and (2) the 7-8 components with the largest peaks, each calculated as the mean frequency across consecutive 5-msec time frames during the first 100 msec of each sound (see Table 2). Only centroid values computed from peak spectral information correlated strongly with the second dimension of the EXSCAL solution.…”
Section: Methodsmentioning
confidence: 99%